The Unbearable Lightness of Data: Touloukian's Quest and Why It Still Matters. - David Flaxbart (Issues in Science and Technology Librarianship, 2012)
The author discusses the work of physicist Y. S. Touloukian on information retrieval which is the "Retrieval Guide." It was Touloukian's try to resolve the problem of using text to search for numbers by coming up with an evaluated bibliography of publications reporting physical property data for various materials.